Sobre efeitos quânticos da interação de um dipolo elétrico induzido com campos externos - Oliveira, Abinael de Brito (2017)
We analyze the appearance of bound states in a Landau-type system for a neutral particle (atom/molecule) with induced electric dipole momentum, in the presence of a conﬁguration of crossed electric and magnetic ﬁelds of the following scalars potential: one which is proportional to the radial distance and the other which is a Coulomb-type. Next, we consider this system under rotational eﬀects and we determined the allowed energy levels. In the search for analytical solutions for the Schro¨dinger equation we show that the energy states of a Landau system for an atom with an induced electric dipole moment subject to potential conﬁners depend on the parameters that characterize both electric and magnetic ﬁelds, besides they also depend on the potential and on the numbers quantum {n,l} of the system. Moreover, the levels found in this investigation are diﬀerent from the Landau levels presented in reference: C. Furtado, J. R. Nascimento, e L. R. Ribeiro (2006) [1]. And for the case where we treat the system in a rotating frame, we ﬁnd the spectrum with the characterizing parameters for the lectromagnetic ﬁeld, with the quantum numbers {n,l} besides its uniform angular speed of rotation. Furthermore, we observe that it is possible to recover the quantization of Landau subject to the potential conﬁners if we take the limit at when the angular velocity disappears.